The practice and challenges of e-Government in Nigeria in the 21st century - Yahaya, Yusuf Musa; Idris, Hassan Abubakar (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
This paper investigates the state of the present condition of e-government commitment in Nigeria. It also, examines the difficulties encountered in the implementation process.Layne and Lee (2001) “Stages of growth theory” was adopted to explain the position of Nigeria in the implementation and the challenges it faced on e-government.To do this,this paper used secondary data as a source to collect different articles and report.This paper finds that while e-government is present in Nigeria, it is still in its initial stage.Not only have that, the environment lacked many prerequisites for the survival and continued maintenance of e-governance due to many factors such as inadequate electricity, technical expertise etcetera.It is therefore suggested that both the government and the stakeholders should take it up as a challenge to find quick and lasting solutions to them. There must also be political will and government should have its administrative staff retrained in IT to properly manage the facilities and infrastructure necessary for e-government.